Improving mother's ability to regulate emotions to build family resilience in the New Sidoarjo Babywearer Community - Zaki Nur Fahmawati; Niko Fediyanto; Lely Ika Mariyati (Community Empowerment, 2023)
A mother is the main caregiver as well as carrying out multiple roles so that she is more vulnerable to pressure in most families. Mothers also tend to feel sad, tired, lonely, nervous, anxious and more easily worried. Generally, parenting stress is triggered by the mother's disproportionate burden on raising children. This community service aims to provide education to mothers to optimize their role in the family to build family resilience. The program was carried out online and offline with 30 members of the New Sidoarjo Babywearer community who are part of Indonesia Baby Wearers. The implementation method used is lectures, discussions, hands-on practice and assignment. The analysis used to evaluate the success of this psychoeducation is by pretest and posttest. The results obtained were an increase in participants' knowledge based on an average pre-test score of 56.66% and an average post-test of 84.65%. Thus, psychoeducation is effective in increasing mothers' understanding of parenting stress and regulating emotions.